PENGARUH PENDAMPINGAN GIZI ONLINE TERHADAP PENGETAHUAN DAN KONSUMSI ENERGI IBU HAMIL KEK DI PUSKESMAS BULULAWAN - NADHIFATUL HIKMIYAH (HARENA : Jurnal Gizi, 2021)
Background : According to the results of the "Si Canting" Application Survey in Bululawang District (2019), the prevalence of pregnant women with KEK is high, namely 39.02%, compared to the Health Center Work Assessment Indicator for the prevalence of pregnant women with KEK which is <19.7%. The purpose of this study : to study differences in knowledge, energy consumption before and after online mentoring about nutrition (E-Booklet, Video and E-Booklet and Video media) on pregnant women in the Bululawang Community Health Center. Method : This type of research is Pre-experimental studies with randomized whitout control pre and posttest design with a total sample of 90 pregnant women, divided into 3 groups and receiving different treatment. The independent variables of this research are e-booklet media, video media, e-booklet and video media, while the dependent variable is knowledge and energy consumption. Change in knowledge and energy consumption were analyzed by Paired sample t-test. Research result : There was a significant difference (p = 0.000) in knowledge and energy consumption before and after providing online mentoring both with e-booklets, videos, as well as e-booklets and videos. However, the highest increase of average knowledge (55,6±10,7 to 60,8±11,7) and energy consumption (59,5±17,1 to 68,5±20,1) was in the e-booklet and video media groups. Conclusion: The use of video and e-booklet together in online mentoring of pregnant women has more effect on increasing the knowledge and energy consumption average of respondents compared to using e-booklets only or video only.